2013
DOI: 10.1021/cg301445h
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Tomographic Analyses of CeO2 Nanoparticles

Abstract: A detailed morphological and structural analysis of CeO 2 nanoparticles has been performed using electron tomography in scanning transmission mode in high angle annular dark field. The nanoparticles have been prepared through a solvothermal synthesis assisted by microwave heating. An adequate choice of the synthesis parameters leads to particles with various well-defined morphologies: cubes, octahedrons, and nanorods. In the case of cubic CeO 2 nanoparticles, the three-dimensional analysis allowed us to precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 28 publications
5
95
0
Order By: Relevance
“…Because the cracking fragments for acetaldehyde and the products have considerable overlap in the mass spectrum, the analysis required that QMS mass intensities be corrected. This correction was performed as described previously, 7 by creating a matrix containing the mass fragment intensities for each product (acetaldehyde, H 2 , methane, H 2 O, CO, ethanol, O 2 , CO 2 , 1,3-butadiene, 2-butene, crotyl alcohol, acetone, furan, crotonaldehyde, benzene, and toluene) contributing to the masses of 2, 15,18,28,29,31,32,44,54,56,57,58,68,70,78, and 90 and solving the resulting equation to convert mass intensity to product yield (partial pressure). The mass fragment intensities were corrected for QMS sensitivity parameters, including ionization efficiency, quadrupole transmissions, and multiplier gain, as described previously.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the cracking fragments for acetaldehyde and the products have considerable overlap in the mass spectrum, the analysis required that QMS mass intensities be corrected. This correction was performed as described previously, 7 by creating a matrix containing the mass fragment intensities for each product (acetaldehyde, H 2 , methane, H 2 O, CO, ethanol, O 2 , CO 2 , 1,3-butadiene, 2-butene, crotyl alcohol, acetone, furan, crotonaldehyde, benzene, and toluene) contributing to the masses of 2, 15,18,28,29,31,32,44,54,56,57,58,68,70,78, and 90 and solving the resulting equation to convert mass intensity to product yield (partial pressure). The mass fragment intensities were corrected for QMS sensitivity parameters, including ionization efficiency, quadrupole transmissions, and multiplier gain, as described previously.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…21,27,28 However, recent results suggest that, depending on the annealing treatment, CeO 2 wires and rods could actually expose a variety of facets, including {111} facets, and possess large numbers of nanoscopic structural defects. 29 Here, the structure of the CeO 2 wires will be referred to as a defect structure. CeO 2 is known to possess strong basic sites and weaker acidic sites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Determining such relationships is particularly important for understanding the surface chemical properties of REO nanoparticles, which expose multiple types of facets. 28,29 Recent work has focused on the chemical properties of CeO 2 (100) in the form of well-defined thin films 30 as well as nanocrystal shapes. 31 Researchers have also shown that both CeO x (100) and (111) orientated nanoparticles can coexist on Cu(111), 32,33 and it has been reported recently that CeO x (100) islands can be produced on Ru(0001) by annealing in an oxygen-depleted environment.…”
Section: Introductionmentioning
confidence: 99%
“…Florea et al performed tomographic analysis of CeO 2 cubes, octahedra, and wires to give an insight into the nature of the surface terminations and faceting ( Figure 2) [97]. For example, ideal cubes would expose six {100} facets, while octahedra would expose only {111} facets.…”
Section: Structural Properties Coordination Numbers and Surface Stamentioning
confidence: 99%
“…For example, ideal cubes would expose six {100} facets, while octahedra would expose only {111} facets. However, tomographic studies found that the rods are porous and the surface is rough, resulting in a highly defective surface that can have pentagonal or hexagonal geometries depending on the synthesis conditions and diameter of the rods [97]. Therefore, it is important to be able to determine the extent of faceting on their surfaces, edges, and corners.…”
Section: Structural Properties Coordination Numbers and Surface Stamentioning
confidence: 99%